2D Storytelling: Responsiveness Among Malaysian Society of Covid-19 - Shazwan Harris Bin Mohd Saad; Azir Redza Bin Norizan (Journal of Computing Technologies and Creative Content, 2023)
This purpose of this research is to create a storytelling video about responsiveness among Malaysian society of COVID-19 using 2D animation which provides storytelling contents on the topic. This study is focusing on creating storytelling that will expose storytelling animation. ADDIE model is the most suitable method to use for the project as it consists all of the methods which are analysis, design, development, implementation and lastly evaluation. Overall, this study will provide users with self-awareness stepped forward knowledge of the coronavirus and a useful understanding of sanitation, self-care, and infected viruses, particularly whilst defined in the storytelling technique. Through this storytelling, it's miles anticipated that the reality approximately the historic tale thru this lively 2D storytelling may be transmitted to our network and could have a fantastic impact on the country of Malaysia in the future.